Exogenous Autoinducer-2 Rescues Intestinal Dysbiosis and Intestinal Inflammation in a Neonatal Mouse Necrotizing Enterocolitis Model - Ji, Yan-Chun; Sun, Qian; Fu, Chun-Yan; She, Xiang; Liu, Xiao-Chen; He, Yu; Ai, Qing; Li, Lu-Quan; Wang, Zheng-Li (Frontiers in Cellular and Infection Microbiology, 2021)
Autoinducer-2 (AI-2) is believed to be a bacterial interspecies signaling molecule that plays an important role in the regulation of the physiological behaviors of bacteria. The effect of AI-2 on the process of necrotizing enterocolitis (NEC) is unknown, and the aim of this study was to study the effect of AI-2 in a mouse NEC model. C57BL/6 mouse pups were randomly divided into three groups: the control group, the NEC group, and the NEC+AI-2 (NA) group. Exogenous AI-2 (500 nM) was added to the formula milk of the NA group. The concentrations of fecal AI-2 and flora were tested. The expression of cytokines, TLR4 and NF-κB in intestinal tissue was detected. The AI-2 level was significantly decreased in the NEC group (P<0.05). Compared with the NEC group, the intestinal injury scores, expression of TLR4, NF-kB, and proinflammatory factors (IL-1β, IL-6, IL-8 and TNF-α) were reduced, and expression of anti-inflammatory factor (IL-10) was increased in the NA group mice (P<0.05). At the phylum level, the Proteobacteria abundance in the NA group was significantly increased, while the Bacteroidota abundance in the control group was significantly increased (P<0.05). At the genus level, Helicobacter and Clostridium_sensu_stricto_1 exhibited significantly greater abundance in the NEC group than in the other two groups, while Lactobacillus had the opposite trend (P<0.05). In addition, the abundances of Klebsiella, Rodentibacter and Enterococcus were significantly higher in the NA group than in the NEC and control groups (P < 0.05). Exogenous AI-2 partially reverses flora disorder and decreases inflammation in an NEC mouse model.